Fortune favors the brave: tactical behaviors in the middle-distance running events at the 2017 IAAF World Championships - Casado, A.; Renfree, A. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To assess tactical and performance factors associated with progression from qualification rounds in the 800-m and 1500-m running events at the 2017 International Association of Athletics Federations World Championships. Methods: Official results were used to access final and intermediate positions and times, as well as performance characteristics of competitors. Shared variance between intermediate positions and rank order lap times with finishing positions were calculated, along with probability of automatic qualification, for athletes in each available race position at the end of every 400-m lap. Differences in race positions and lap times relative to season`s best performances were assessed between automatic qualifiers, fastest losers, and nonqualifiers. Results: Race positions at the end of each 400-m lap remained more stable through 800-m races than 1500-m races. Probability of automatic qualification decreased with both race position and rank order lap times on each lap, although rank order lap times accounted for a higher degree of shared variance than did intermediate position. In the 1500-m event, fastest losers ran at a higher percentage of season`s best speed and adopted positions closer to the race lead in the early stages. This was not the case in the 800-m. Conclusions: Intermediate positioning and the ability to produce a fast final race segment are strongly related to advancement from qualification rounds in middle-distance running events. The adoption of a more "risky" strategy characterized by higher speeds relative to season`s best may be associated with an increased likelihood of qualification as fastest losers in the 1500-m event.